DIELECTRIC PROPERTIES AND THERMAL CONDUCTIVITY OF HDPE AND PS - Ahmed, Hameed; Ali, Shakhawan (Iraqi Journal of Science, 2024)
Dielectric constant (ε ′ ) over the frequency range 1KHz-1MHz and thermalconductivity (k) have been measured for high-density polyethylene (HDPE) andpolystyrene (PS) (with thicknesses 1.6 and 1.1 mm respectively and all withdiameter 3.2 cm), in the temperature range 30-110°С, It has been found that thedielectric constant is almost frequency independent and slightly temperaturedependent, this reveals the fact that these polymers are non-polar. However, therewas a significant effect of temperature on the thermal conductivity of the samples,especially at Tg of PS and Tm of HDPE.